2005
DOI: 10.1002/bmc.411
|View full text |Cite
|
Sign up to set email alerts
|

Determination of enro?oxacin and its primary metabolite, cipro?oxacin, in pig tissues. Application to residue studies

Abstract: A simple and sensitive HPLC method has been developed for the simultaneous determination of enrofloxacin (ENR) and ciprofloxacin (CIP) in pig tissue using difloxacin (DIF) as internal standard. Tissue sample preparations were carried out by adding phosphate buffer (pH 7.4, 0.1 m), followed by extraction with trichloromethane. Fluoroquinolones were separated on a reversed-phase column and eluted with aqueous buffer solution-acetonitrile (80:20, v/v). The concentrations of CIP, ENR and DIF eluted from the column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
2
4
0
2
Order By: Relevance
“…After 5 days of decontamination, the concentration of ENR and CP in each tissue were lower compared with MRL values regulated by the European Union 1 . Similar results were obtained in a previous study at a daily dose of 5 mg/kg ENR (5%) for 5 consecutive days (Garcia et al, 2005). However, in this study the administration dosage was 10 mg/kg EEG (10% ENR), which doubled that in previous work by Garcia (Garcia et al, 2005), but the ENR and CP concentrations were lower than the results by Garcia for the duration of the experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After 5 days of decontamination, the concentration of ENR and CP in each tissue were lower compared with MRL values regulated by the European Union 1 . Similar results were obtained in a previous study at a daily dose of 5 mg/kg ENR (5%) for 5 consecutive days (Garcia et al, 2005). However, in this study the administration dosage was 10 mg/kg EEG (10% ENR), which doubled that in previous work by Garcia (Garcia et al, 2005), but the ENR and CP concentrations were lower than the results by Garcia for the duration of the experiment.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained in a previous study at a daily dose of 5 mg/kg ENR (5%) for 5 consecutive days (Garcia et al, 2005). However, in this study the administration dosage was 10 mg/kg EEG (10% ENR), which doubled that in previous work by Garcia (Garcia et al, 2005), but the ENR and CP concentrations were lower than the results by Garcia for the duration of the experiment. This result showed that 10% EEG had a faster elimination ratio in each tissue than Garcia's work.…”
Section: Discussionsupporting
confidence: 92%
“…Methanol or acetonitrile often used in mobile phase were not compatible with many CL systems, but compatible with this CL system. Several mobile phases have been reported for the separation of QNs on a reversed phase column, such as acetonitrilewater [18,19,21,24,25], methanol-water [22], acetonitrilemethanol-water [17,23] and acetonitrile-tetrahydrofuran-water [20]. The ternary mixtures of acetonitrile-methanol-water (v/v/v) 3:15:82 were found to be suitable for good separation of these compounds and compatible with the CL system.…”
Section: Optimization Of Hplc Conditionsmentioning
confidence: 95%
“…Για το πρώτο στάδιο της εκχύλισης, στη βιβλιογραφία, χρησιμοποιούνται υπερκάθαρο νερό [91,111,119,130] και υδατικά διαλύματα, όπως διαλύματα NaOH [133,117,118], πυκνή αμμωνία [94,99,114,125,128,134] και διαλύματα HCl [96,97]. Επίσης χρησιμοποιούνται ρυθμιστικά διαλύματα σε pH 7.0 [94,131,133], pH 4.1 [127], pH 7.4 [103,110,112,122,132,136], pH 6.0 [129] και pH 9.1 [98].…”
Section: προκατεργασία δειγμάτων τροφίμων ζωικής προέλευσηςunclassified
“…Ακετονιτρίλιο [98-100, 104, 114, 116, 121, 125, 128], μεθανόλη [100], διχλωρομεθάνιο [91,92,109,117,121,130,132,133,136,137], εξάνιο [93,98,100,102,107,111,136], ακετόνη [102], χλωροφόρμιο [102,112,114] και ισοπροπανόλη [129] είναι οι συνηθέστεροι οργανικοί διαλύτες που χρησιμοποιούνται για την εκχύλιση των (φθορο)κινολονών από τα εξεταζόμενα υποστρώματα. Συχνά χρησιμοποιούνται διαλύματα των παραπάνω διαλυτών με κάποιο οξύ, όπως μίγμα μεθανόλης με οξικό οξύ [93,107,109], με φωσφορικό οξύ [108], με μίγμα φωσφορικού και υπερχλωρικού οξέος [106,113], διάλυμα αιθανόλης με οξικό οξύ [126] και διάλυμα CH 3 CN με άλας Na 2 SO 4 [95], με τριχλωρο-οξικό οξύ [101,111,120], με οξικό οξύ [104] και με φωσφορικό οξύ [115].…”
Section: προκατεργασία δειγμάτων τροφίμων ζωικής προέλευσηςunclassified